Pricing and profiting in copyright: introducing an Islamic perspective. Issue 2 (May 2020) - Adam, Ainee
Abstract : The economic rights granted to copyright holders are, at times, an obstacle to the public's right of access to knowledge as the works are priced beyond the means of their consumers. Recognizing this, the three-step test in Article 13 of the Trade-Related Aspects of Intellectual Property Rights Agreement provides exceptions and limitations to the copyright holders' economic rights. It is, however, arguable that the test is inadequate in balancing the rights and interests of the copyright holders and the public. It is observed that most of the available literature on this issue is based on Western principles and thought. This article, therefore, proposes that scholarship from an alternative set of knowledge could potentially shed some light on the matter. In particular, it suggests that an Islamic perspective on pricing and profiting could provide a more appropriate balance that would grant equitable access to knowledge, research and education to the general public, while ensuring that copyright holders (and authors) remain incentivized to produce high-quality literary work. In so doing, the article introduces one of the first steps in applying Islamic economic principles to contemporary copyright issues.